ENHANCING MATHEMATICAL COMPETENCIES IN TVET: LESSONS FROM ENGINEERING STAFF IN MALAYSIAN MANUFACTURING SECTORS. - SAHRONI, MOHAMAD NORHAKIM BIN; Mohd Puzi , Nur Izrah Binti; Subaryo (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2024)
Technical and Vocational Education and Training (TVET) programmes are crucial in providing the skilled workforce required by various industrial sectors in Malaysia. Mathematical knowledge and skills are essential foundations in TVET programmes as they equip students with the numerical skills, measurement, problem-solving abilities, and logical reasoning needed in various skill areas. However, studies show that TVET students face weaknesses in mathematics, such as poor understanding of basic concepts, weak calculation and problem-solving skills, and difficulties in applying mathematical concepts to new situations related to their skill areas. To overcome these weaknesses, new approaches in mathematics teaching and learning are needed, including emphasis on mathematical applications in skill areas, more effective pedagogy, and adequate training for instructors. Due to the complexity of problems that engineering staff need to solve, they require training in real-life problem-solving scenarios. MBOT accreditation guidelines emphasise the critical importance of developing mathematical competencies in producing versatile graduates who can apply mathematical knowledge to address real-world challenges in their respective disciplines. Therefore, a phenomenological approach was used in this study to identify mathematical competencies (MC) among engineering staff serving in manufacturing workplaces. Data were collected through intensive interviews, and phenomenological reduction techniques were used for data analysis. The findings show that mathematical competencies frequently used by engineering staff include Manage to Gather Data Problem Handling, Tools management, and Self-mathematical Decision. This study can provide input to instructors on developing mathematical competencies relevant to real-life problem-solving in TVET academic activities and programmes at their respective institutions.